Measuring Values in Environmental Research: A Test of an Environmental Portrait Value Questionnaire - Bouman, Thijs; Steg, Linda; Kiers, Henk A. L. (Frontiers in Psychology, 2018)
Four human values are considered to underlie individuals’ environmental beliefs and behaviors: biospheric (i.e., concern for environment), altruistic (i.e., concern for others), egoistic (i.e., concern for personal resources) and hedonic values (i.e., concern for pleasure and comfort). These values are typically measured with an adapted and shortened version of the Schwartz Value Survey (SVS), to which we refer as the Environmental-SVS (E-SVS). Despite being well-validated, recent research has indicated some concerns about the SVS methodology (e.g., comprehensibility, self-presentation biases) and suggested an alternative method of measuring human values: The Portrait Value Questionnaire (PVQ). However, the PVQ has not yet been adapted and applied to measure values most relevant to understand environmental beliefs and behaviors. Therefore, we tested the Environmental-PVQ (E-PVQ) – a PVQ variant of E-SVS –and compared it with the E-SVS in two studies. Our findings provide strong support for the validity and reliability of both the E-SVS and E-PVQ. In addition, we find that respondents slightly preferred the E-PVQ over the E-SVS (Study 1). In general, both scales correlate similarly to environmental self-identity (Study 1), energy behaviors (Study 1 and 2), pro-environmental personal norms, climate change beliefs and policy support (Study 2). Accordingly, both methodologies show highly similar results and seem well-suited for measuring human values underlying environmental behaviors and beliefs.